PENERAPAN MODEL ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, DAN SATISFACTION (ARIAS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV C SDN 164 PEKANBARU - Rahayu, Sri; ', Lazim; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is students lower score in learning social of class IV C SDN 164 Pekanbaru, it can be seen from 42 students of class IV C, 20 students (47,62%) got lower score and 22 students (52,38%) got higher score with the mean score is 70,31. The KKM of this school is 75. According to the problem, the researcher has conducted a classroom action research by implementing Assurance, Relevance, Interest, Assessment, and Satisfaction (ARIAS) model. In cycle I, the percentage of teacher’s activity in first meeting is adequate 55%. In the second meeting, it increased to 65% with good category. In cycle II, first meeting it increased to 80% with good category in first meeting and second meeting indicated in very good category 90%. In cycle I, the percentage of student’s activity in first meeting is adequate 60%. In the second meeting, it increased to 75% with good category. In cycle II, first meeting it increased to 80% with good category in first meeting and second meeting indicated in very good category 90%. An average score of student’s learning result before implementation ARIAS model was 70,31 it increase to 79,29 in cycle I, and 81,55 in cycle II. The classical completeness was achieved in both cycle. In conclusion, the implementation ARIAS model can improve student’s learning result in social subject of class IV C of SDN 164 Pekanbaru.Keywords: ARIAS model, learning result of social subject